Cognitive testing of an instrument to evaluate acceptability and use of pre‐exposure prophylaxis products among women. Issue 1 (23rd July 2019) - Zissette, Seth; Atujuna, Millicent; Tolley, Elizabeth E.; Okumu, Eunice; Auerbach, Judith D.; Hodder, Sally L.; Aral, Sevgi O.; Adimora, Adaora A.
Summary: Given the range of pre‐exposure prophylaxis (PrEP) products currently being tested to prevent HIV in women, a standardized Acceptability and Use of PrEP Products Among Women Tool may facilitate comparisons of product acceptability and use across different geographies, trials, and users. We conducted three rounds of cognitive interviewing over 2 months in 2016, with 28 South African women who had experience participating in a range of PrEP product trials. The final instrument contained 41 items, including five new items that improved construct validity and 22 items modified for clarity. Changes were made due to unclear wording, difficulty answering, participant embarrassment, low response variability, and administrative formatting. Cognitive interviewing provided a means to address issues that would have inhibited this tool's ability to accurately collect data otherwise. This rapid, low‐cost study provided valuable insight into participants' understanding of questions and demonstrated the utility of cognitive interviewing in international clinical trials.